Prevalence of Type II Diabetes Mellitus and Perioperative Outcomes in Patients Undergoing Cardiac Surgery with Cardiopulmonary Bypass at a Tertiary Cardiac Center in Nepal - Amatya, Ashish; Pudasaini, Ashok; Bajrachaya, Smriti M.; Shrestha, Battu K; Bhandari, Sandip; Khadka, Abhay; Pandey, Prasanna; Poudel, Swastika (Nepalese Heart Journal, 2026)
Background and aim: Diabetes mellitus (DM) is a major contributor to cardiovascular morbidity and mortality worldwide. Patients with DM undergoing cardiac surgery with cardiopulmonary bypass (CPB) experience higher rates of perioperative complications. National data describing the burden of diabetes and associated outcomes among cardiac surgical patients in Nepal remain limited. Methods: A retrospective observational study was conducted at a tertiary cardiac center in Kathmandu. Consecutive adult patients undergoing cardiac surgery with CPB between June 2022 and June 2023 were included. Demographic, clinical, and perioperative variables were collected and analyzed descriptively, including age, sex, body mass index (BMI), American Society of Anesthesiologists (ASA) physical status, glycated hemoglobin (HbA1c), type of surgery, acute kidney injury (AKI), surgical site infection (SSI), length of intensive care unit (ICU) stay, re-exploration, in-hospital mortality. Results: Type II DM was identified in 86 of 406 patients (21.2%). %). The median age was 60.5 years in diabetic patients and 51.5 years in non-diabetic patients, and BMI distributions were descriptively analyzed for both groups. Coronary artery bypass grafting (CABG) was performed in 73 diabetic patients (84.8%). In the diabetic cohort, acute kidney injury (AKI) was observed in 32.6% (vs. 27.5% in non-diabetics), surgical site infection in 4.7% (vs. 0%), re-exploration in 17.4% (vs. 15.9%), and in-hospital mortality in 22.1% (vs. 14.1%). The median glycated hemoglobin level (HbA1c) among diabetic patients was 7.0% (IQR, 6.0–7.8). Conclusion: This study outlines the specific clinical distribution of diabetes mellitus in this cohort. The descriptive data support establishing routine screening pathways to optimize perioperative care.